MicroPET/CT Assessment of Minocycline Effects on Anesthetic-Induced Neuronal Injury in Developing Rats - Xuan Zhang; Merle G Paule; Mackean Maisha; Glenn D Newport; Marc S Berridge; Scott M Apana; William Slikker Jr; Cheng Wang (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Ketamine is a dissociative anesthetic that is frequently used for the induction and maintenance of general anesthesia in children. It has been reported that blockade of NMDA receptors by ketamine may cause neurotoxicity in neonatal rats when given over a 12 hour period during the brain growth spurt. Noninvasive, quantitative imaging of rodent brains may allow for the detection of functional, morphological and metabolic alterations induced by ketamine. Since it is known that level of the mitochondrial translocator protein (TSPO), formerly known as the peripheral benzodiazepine receptor (PBR) increase in areas of neuronal injury following exposure to neurotoxicants, TSPOs are widely recognized as important targets for imaging using positron emission tomography (PET). In this study, the effect of ketamine on the uptake and retention of [18F]-FEPPA (a TSPO ligand) in the brains of rats and the potential protective effect of minocycline, an anti-infl ammatory agent, on anesthetic-induced neuronal cell death were investigated using microPET/CT imaging. On postnatal day 7 (PND 7), rat pups in the experimental group were exposed to 6 injections of ketamine (20 mg/kg at 2 h intervals) with or without minocycline (45mg/ kg i.p. 30 minutes prior to, and 4 hours after exposure); control pups received 6 injections of saline. On PNDs 14, 21, 28 and 35, [18F]-FEPPA (18.5 MBq) was injected into the tail vein of treated and control rats and microPET/CT images were obtained over the next 90 minutes. Radiolabeled tracer accumulation in regions of interest (ROIs) in the frontal cortex was converted into Standard Uptake Values (SUVs). In PND 14 and 21 rats the uptake of [18F]-FEPPA was signifi cantly increased and the duration of tracer wash-out was prolonged in ketamine-treated rats. The increased uptake of the tracer was attenuated by the co-administration of minocycline. As expected, no signifi cant difference in radiotracer uptake in the frontal cortex was observed at 28 or 35 days after anesthesia. This preliminary study demonstrates that microPET imaging is capable of distinguishing differences in retention of [18F] -FEPPA in the brains of rodents and suggests that this approach may provide a minimally-invasive biomarker of pathogenic process associated with neurotoxicity induced by ketamine. Minocycline effectively blocks the neuronal injury caused by ketamine anesthesia in the developing rat brain.